Evaluasi penambahan probiotik (Lactobacillus sp) cair dan padat dalam pakan terhadap penampilan produksi ayam petelur (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
This research aims to discover the effect of powder and liquid probiotic addition in laying’s feed towards their production. This research involved 144 Isa Brown layer with 6 months (24 weeks) age and liquid probiotic containing Lactobacillus sp bacteria with the composition of 1,4 x 1010 cfu/ml, while the solid probiotic that was used using skim milk media was processed into powder. The method used was experimental, employing nested Completely Randomized Design (CRD) with 2 factors and 6 actions, in which every action is given 4 times repetition; each repetition consisted of 6 layer. The data was analyzed using variety analysis and examined further by the Duncan test. Research result showed that the addition of powder or liquid Lactobacillus sp probiotic gave a positive effect on consumption amount, feed conversion, HDP, egg mass, IOFC, and egg mass of layer. It can be concluded that the addition of powder probitotic is better than the liquid one, while 0.6% of addition can increase the performance of laying production. Concluded that the addition of probiotics in solid form was better than liquid form, while the level of administration of 0.6% could improve the production of layer.